Inside trade system development in Lithuanian province in 1861-1914 - Aelita Ambrulevičiūtė (Lietuvos Istorijos Studijos)
Till the 1861 years reforms town's and township's dwellers bought goods usually at dolly-shops, shops, markets, and marts. Village dwellers bought items from itemsman's or in the alehouse. Merchants, townspeople, tradesmen used to sell self-made production from workshops or in the markets and marts. Noblemans organized trade at the alehouse. Peasants handled rarely. Only the most sophisticated and minded peasants were engaged in commercial activity.